P861 Novel mutation conferring high-level azithromycin resistance in neisseria gonorrhoeae. (14th July 2019) - Nash, Evelyn; Liu, Hsi; Schmerer, Matthew; Cyr, Sancta St; Sharpe, Samera; Soge, Olusegun; Hardin, Henrietta; Kersh, Ellen; Pham, Cau
Abstract : Background: Azithromycin resistance in Neisseria gonorrhoeae has been attributed to several resistance-associated mutations including mutations in the 23S rRNA genes conferring varying levels of azithromycin resistance. Here, we report the emergence of a novel A to G mutation at the 2058 nucleotide residue (A2058G) in the 23S rRNA genes, in two gonococcal isolates, that confers high-level resistance to azithromycin (HLAziR; ≥ 256 mg/ml). Methods: The collection and antimicrobial susceptibility testing of N. gonorrhoeae isolates were performed as part of the Gonococcal Isolate Surveillance Project (GISP). Isolates with elevated minimum inhibitory concentration to azithromycin (≥ 2 mg/ml) were subjected to molecular analysis using Sanger PCR sequencing and/or whole genome sequencing analysis. Etest ® was performed to confirm azithromycin susceptibility level and to determine the hetero-resistance phenotype (a concentration-dependent response to antibiotic) of the reported isolates. Results: Molecular analysis of GISP isolates from 2014–2018 revealed two isolates collected from two patients having the A2058G mutation in the 23S rRNA genes. One isolate had the HLAziR phenotype and A2058G mutations in all four 23S rRNA. The second isolate had the A2058G mutation in three of the four alleles and displayed a hetero-resistance phenotype (azithromycin MIC ranging from 4 mg/ml to ≥ 256 mg/ml). The wild-type allele was very conducive to A2058G conversion and resulted in a complete HLAziR phenotype. This mutational nucleotide conversion occurred in less than twenty hours after exposure to azithromycin using Etest ® . Conclusion: HLAziR in N. gonorrhoeae had largely been confined to isolates harboring a point mutation at nucleotide residue A2059G of the 23S rRNA genes. The newly discovered A2058G mutation further illuminates the genomic plasticity in N. gonorrhoeae when responding to antibiotic exposure and suggests a rapid recombination frequency between the 23S rRNA alleles at this nucleotide residue. Disclosure: No significant relationships.